2017
DOI: 10.1111/eje.12259
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, depression and suicidal ideation in dental and dental hygiene students

Abstract: These findings suggest the need for introducing preventive measures for such affective states in dental and dental hygiene training programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
5
14

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(130 citation statements)
references
References 17 publications
6
105
5
14
Order By: Relevance
“…Despite the relatively weak relationships found in this study, loneliness should be avoided and treated carefully because suicide causes a serious loss of not only individuals but also the national health workforce. The results showing the occurrence of suicidal ideation throughout life or in the previous year (37.7%-33.4%) were higher than found most previous medical and dental studies [9][10][11][12]14,16,17,[20][21] with the exception of the high prevalence in Taiwan (43.6%) 13 and Pakistan (35.4%). 15 Moreover, the results of our study showed the highest prevalence of suicide attempts compared to all previous studies on medical and dental students.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Despite the relatively weak relationships found in this study, loneliness should be avoided and treated carefully because suicide causes a serious loss of not only individuals but also the national health workforce. The results showing the occurrence of suicidal ideation throughout life or in the previous year (37.7%-33.4%) were higher than found most previous medical and dental studies [9][10][11][12]14,16,17,[20][21] with the exception of the high prevalence in Taiwan (43.6%) 13 and Pakistan (35.4%). 15 Moreover, the results of our study showed the highest prevalence of suicide attempts compared to all previous studies on medical and dental students.…”
Section: Discussionmentioning
confidence: 54%
“…The responses were either "yes" or "no." SPSS v. 21 software was used to analyze the data collected from the completed questionnaires. The descriptive statistics included a frequency table, mean (M), and standard deviations (SD).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dentistry is considered one of the most stressful professions . Occupational stress has been a main factor in the higher risk for suicide amongst dentists; even before graduation, 6% of dental students in the United States tested above the cut‐off for clinically significant suicidal ideation . A systematic review concluded that psychological problems have the strongest association with suicide .…”
Section: Introductionmentioning
confidence: 99%